Rosai-Dorfman disease of the lung. Issue 10 (28th September 2009) - Ali, A; Mackay, D
Abstract : Rosai-Dorfman disease is a rare disorder which seems to involve not only the lymph nodes but most other organs of the body. The case history is presented of a woman who was thought to have atypical carcinoma of the lung but in whom a diagnosis of Rosai-Dorfman disease was eventually made following a range of investigations including CT scans, positron emission tomography (PET) and histological analysis of open lung biopsy specimens. She remains well with no further progression of the disease without treatment. Rosai-Dorfman disease can mimic lung carcinoma and shows increased activity on PET scanning, so histological confirmation should be sought in all cases.